A new Early Jurassic damselfly from the Grand Duchy of Luxembourg (Odonata: Campterophlebiidae). Issue 3 (3rd July 2017) - Nel, André; Weis, Robert
Abstract : Nel, A. & Weis, R . March 2017. A new Early Jurassic damselfly from the Grand Duchy of Luxembourg (Odonata: Campterophlebiidae). Alcheringa 00, 000–000. ISSN 0311-5518. André Nel [anel@mnhn.fr ], Institut de Systématique, Évolution, Biodiversité, ISYEB - UMR 7205 — CNRS, MNHN, UPMC, EPHE, Muséum national d'Histoire naturelle, Sorbonne Universités, 57 rue Cuvier, CP 50, Entomologie, F - 75, 005, Paris, France; Robert Weis [rweis@mnhn.lu ], Musée national d'histoire naturelle, Luxembourg, Section Paléontologie, 25, rue Münster L - 2160 Luxembourg, Grand-Duché de Luxembourg. Gallodorsettia kronzi gen. et sp. nov., the first representative of the damselfly family Campterophlebiidae from the Toarcian of Grand Duchy of Luxembourg, is described herein. Its closest relative is the genus Dorsettia, known from the early Lower Jurassic of UK and China. The Campterophlebiidae seem to be rare in the Early Jurassic of Western Europe, despite being one of the most diverse odonatan families at that time, especially in Asia.